Effect of Ocimum basilicum L. Aerial Parts Extract and Fractions on Morphine Withdrawal Syndrome in Mice - H Hosseinzadeh; M Ramezani; Z Afarin (Institue of Medicinal Plants, ACECR, 2012)
Background: Ocimum basilicum showed antinociceptive activity. The antinociceptive effect was inhibited by naloxone in hot-plate test.   Objective: As O. basilicum antinociceptive activity was inhibited by an opioid antagonist, activity-guided fractionation of methanol extract of this plant was carried out to investigate the isolation of the active component(s) responsible for the alleviation of morphine withdrawal syndrome induced by naloxone.   Methods: Dependence was induced using subcutaneous injections of morphine daily for three days (50, 50 and 75 mg/kg). On the fourth day, morphine was injected two hours prior to the intraperitoneal injection of naloxone. The number of jumps during the 30 minute period after naloxone injection was considered as measure of the withdrawal syndrome. The extract and fractions were injected 30 min prior to morphine injection. The methanol extract of plant was suspended in water and extracted with chloroform. The active chloroform layer was concentrated and partitioned between methanol-water (9:1) and petroleum ether. The extract or fraction was injected intraperitoneally at doses 0.15 - 1.46 g/kg.   Results: The methanol, chloroform and petroleum ether extracts decreased the jumping numbers more than the aqueous and hydro-alcohol extracts. Further fractionation on silica gel column chromatography yielded a fraction, which was 4 times as effective as the crude extract. Conclusion: The results of this study indicated that the plant extracts and fractions containing non- polar component (s) could be useful for the alleviation of morphine withdrawal syndrome